Effect of organic fertilizer on production of corn, sorghum and elephant grass forage - Farias, Iderval; Fernandes, Antônio de Pádua Maranhão; Lira, Mário de Andrade; França, Miguel Paiva; Santos, Venézio Felipe dos (Pesquisa Agropecuaria Brasileira, 2014)
This work was conducted at Estação Experimental São Bento do Una, PE. Brazil, to study the effects of organic fertilizer on corn (Zea mays L.), sorghum (Sorghum bicolor (L.) Moench) and elephant grass (Pennisetum purpureum Schum.) forage. The sources and levels of organic matter were zero, ten, 20 and 30 t/ha of cattle manure and zero, five, ten and fifteen t/ha of poultry bed. The fertilizers were applied annually during the experiment. The corn, sorghum and elephant grass yields were 7.4, 10.0 and 13.3 t/M.S./ha/year, respectively. Corn yield increased linearly with fertilizer levels. Sorghum yields increased quadratically with cattle manure, but increased linearly with poultry bed fertilization. The elephant grass yield increased linearly with cattle manure application but responded as a quadratic curve with poultry bed application. Fertilization did not influence significantly protein content. The cellulose percentage was lower in com followed by sorghum and elephant grass. The organic fertilization did not affect the percentages of maize ear and sorghum panicle in relation to the green and dry weight of the plant. Soil organic matter increased linearly with organic fertilization.